De que periferia estás falando? Da representação artística à representação social da periferia em escolas periféricas de Belém - CASTRO, Fábio Fonseca de (Universidade Caxias do Sul, 2022)
The article discusses the relationship between social representations and artistic representations, observing the receipt of two video clips, both thematising the periphery, by high school students from two schools in the outskirts of Belém (Brasil). We want to understand how a artistic representation contributes to conform a social representation on the social dialogic process and about the liminality between artistic representations and media representations. The objective is to understand the dynamic role of the central nucleus of the representations, structured, as demonstrated by observation, through the dialogical process inherent to the social experience.